Plexiform schwannoma mimicking a salivary gland tumor: An unusual case report diagnosed in pediatric patient - Santos, Jean Nunes dos (2011)
State University of Feira of Santana. Consultant in Oral Pathology. Feira de Santana, BA, Brasil / Federal University of Bahia. Department of Oral Pathology. Salvador, BA, Brasil